Didactic Proposal Framed Within Sustainable Development Goal 5 and Gender Perspective Education Through the Film Princess Mononoke in University-level English Teaching: Propuesta didáctica enmarcada en el Objetivo de Desarrollo Sostenible 5 y en la educación con perspectiva de género a través de la película La princesa Mononoke en la enseñanza universitaria del inglés (Papeles, 2024)
Introduction: This study provides a didactic application of the 2030 Agenda focused on Sustainable Development Goal (SDG) 4 (Quality Education) and from which SDG 5 (Gender Equality) is included, incorporating the pedagogical principles of Education with Gender Perspective (EGP) through the film Princess Mononoke (1997), directed by Hayao Miyazaki, due to its thematic relevance to gender issues and female empowerment. The specific objectives of the study include to design and implement a didactic proposal to work on gender equality as a global issue in tertiary English teaching through the film Princess Mononoke (1997) and to gather students’ opinions on the pedagogical proposal they participated in. Methodology: The methodology used is mixed, encompassing qualitative-descriptive aspects associated with the observation of students’ performance in the activities related to the film and gender issues. Quantitative data includes the results from a table of evaluation filled in by both the professor and the students and a questionnaire that the students completed anonymously at the end of the sessions. Results and discussion: The results indicate that the selected scenes and the proposed activities enable students to delve deeper into gender equality, with special reference to female empowerment. Conclusions: It is confirmed that the proposal presented proves effective in addressing SDG 5 in university English teaching, fostering reflection on gender equality as a global issue.
Keywords: Sustainable Development Goals (SDG); education with gender perspective; female empowerment; tertiary education; teaching-learning process